2004
DOI: 10.2174/1568026043451339
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to Understand the Molecular Basis of Hypertension Through Drug:Membrane Interactions

Abstract: Biological membranes play an essential role in the drug action. They constitute the first barrier for drugs to exert their biological action. AT1 antagonists are amphiphilic molecules and are hypothesized to act on AT1 receptor through incorporation (first step) and lateral diffusion through membrane bilayers (second step). Various biophysical methods along with Molecular Modelling were applied in order to explore the plausible two step proposed mechanism of action for this class of antihypertensive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 0 publications
5
19
0
Order By: Relevance
“…Furthermore, losartan decreased the mobility of the lipid molecules, particularly the mobility of the alkyl chains, and increased the order of the bilayer. The information derived from the presented study is in agreement with the combined results obtained with DSC, Raman, 13 C-MAS, 31 P CP/MAS NMR, and EPR, all concluding that losartan anchors in the realm of the headgroup region (34,35).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, losartan decreased the mobility of the lipid molecules, particularly the mobility of the alkyl chains, and increased the order of the bilayer. The information derived from the presented study is in agreement with the combined results obtained with DSC, Raman, 13 C-MAS, 31 P CP/MAS NMR, and EPR, all concluding that losartan anchors in the realm of the headgroup region (34,35).…”
Section: Discussionsupporting
confidence: 88%
“…The application of the CP 31 P NMR broadline simulations suggested that losartan was localized in the zone of the hydrophilic headgroup (34,35). Furthermore, losartan decreased the mobility of the lipid molecules, particularly the mobility of the alkyl chains, and increased the order of the bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since MD analysis has been performed for both CB1 and CB2 receptors, results can be useful for synthetic chemists to produce more selective CB compounds. The localization of AMG3 at the binding sites of the CB1 and CB2 receptors are in the core region of TM3-TM7 in accordance with reported biophysical crystallographic and modelling studies [102][103][104][105][106][107][108][109][110][111][112][113][114][115] (Fig. 3).…”
Section: Strategy Applied For a System-iisupporting
confidence: 89%
“…Such pathway has been proposed for a number of ligands (Fig. 5B) like the endogenous CB 1 cannabinoid receptor agonist anandamide, the synthetic ␤ 2 -adrenergic receptor agonist salmeterol, the AT 1 -type angiotensin II receptor antagonist losartan and the D 2 -dopamine receptor antagonist spiperone (Anderson, 1993;Anderson et al, 1994;Theodoropoulou and Marsh, 1999;Zoumpoulakis et al, 2003;Mavromoustakos et al, 2004;Makriyannis et al, 2005;Tian et al, 2005;Packeu et al, 2008). Anadamantine (Fig.…”
Section: Lateral Translocation Between the Receptor's Transmembrane ␣mentioning
confidence: 99%